The development of proofs in analytical mathematics for undergraduate students - Ali, Maselan; Sufahani, Suliadi Firdaus; Hasim, Nurnazifa; Rusiman, Mohd Saifullah; Roslan, Rozaini; Mohamad, Mahathir; Khalid, Kamil (2018)
Proofs in analytical mathematics are essential parts of mathematics, difficult to learn because its underlying concepts are not visible. This research consists of problems involving logic and proofs. In this study, a short overview was provided on how proofs in analytical mathematics were used by university students. From the results obtained, excellent students obtained better scores compared to average and poor students. The research instruments used in this study consisted of two parts: test and interview. In this way, analysis OF students actual performance can be obtained. The result of this study showed that less able students have fragile conceptual and cognitive linkages but the more able students use their strong conceptual linkages to produce effective solutions